Переходные характеристики пироэлектрических детекторов - Бондаренко, Александр Юрьевич; Ключник, Игорь Иванович; Бембель, Александр Дмитриевич (НТУ "ХПІ", 2018)
В работе рассматриваются динамические характеристики пироэлектрических детекторов, а именно переходные процессы при их реакции на импульсное тепловое воздействие. Отмечены особенности переходных характеристик как при нагревании, так и при охлаждении детектора. Полученные зависимости использованы при разработке симулятора пироэлектрического преобразователя, с помощью которого возможен анализ и визуализация характеристик как существующих детекторов, так и вновь разрабатываемых. Указаны примеры использования пиродетекторов, для которых переходные характеристики наиболее важны. Разработанный симулятор может быть использован и в учебных целях.

In this paper, we consider the transient characteristics of a standard single-chip pyroelectric detector. Output voltage transients are easy to measure. Direct measurement of the pyroelectric current presents some difficulties, associated primarily with a sharp jump in the initial crystal current and the input capacitance of the measuring device. Direct measurement of the crystal temperature is impossible, so it can be obtained either by modeling based on known processes, or by mathematical transformations of the results of measuring the thermal time constant with respect to the pyroelectric current. Dynamic characteristics in the time domain, particularly, transient responses are considered. Specificities of transient responses when the detector is heated and cooled, are noted. Results obtained applied to a simulator of a pyroelectric detector. The simulator plots the transient responses. It allows to change a number of parameters to receive new results. The latter is important for not only modeling or analysis existing devices, but also designing new ones. Some applications of pyroelectric detectors are pointed. The simulator is free and can be used in labs at the Universities, or anywhere in the world. Identification of differences between the movement of a person and, for example, the movement of ascending heated air currents or cold drafts in motion sensors occurs precisely in the transient response of the detector output voltage, decomposition of which into Fourier series, in this case, is unacceptable. Thus, for a number of applications of pyroelectric detectors, the problem of research and transient characteristics is relevant. Identification of differences between the movement of a person and, for example, the movement of ascending heated air currents or cold drafts in motion sensors occurs precisely in the transient response of the detector output voltage, decomposition of which into Fourier series, in this case, is unacceptable. Thus, for a number of applications of pyroelectric detectors, the problem of research and transient ch aracteristics is relevant.
Transient processes in a pyroelectric detector
Keywords: тепловой поток; пироэлектрический ток; выходное напряжение; симулятор пироэлектрического преобразователя; heat flow; pyroelectric current; pyroelectric output voltage; simulator of a pyroelectric detector